Chemical analysis of some Pakistani Portland cement/clinker and their compliance with ASTM standards - Rasheed, Sufian; Ullah, Niamat; Ullah, Amir (European Journal of Chemistry, 2020)
This is a quality control study and analysis of Portland cement taken from four Pakistani cement plants (Deewan, Kohat, Lucky and Maple Leaf). These four samples were analysed and the determination of major oxides present was carried out. Loss on ignition and the percentage of insoluble residue was also determined. Our research shows percentage of major oxides present in these four samples i.e. calcium oxide, silicon dioxide, aluminium oxide, iron oxide, sulphur trioxide and magnesium oxide. According to the American Society for Testing and Materials Cement (ASTM C150), the percentage of these oxides, loss on ignition and insoluble residue of these four plants are within the specified quality control range. The present study compared the quality of different oxides at the Portland cement brands in Pakistan. The percentages of SiO2,SO3, CaO, Al2O3,MgO and Fe2O3 were calculated according to American Society for Testing and Materials (ASTM C150) uniform standards. The percentages of all of the brands were within the limits specified by the standard (ASTM C150).